2017
DOI: 10.1002/ddr.21411
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction of a Gabapentin‐ Mangiferin Combination in Formalin‐Induced Secondary Mechanical Allodynia and Hyperalgesia in Rats Is Mediated by Activation of NO‐Cyclic GMP‐ATP‐Sensitive K+ Channel Pathway

Abstract: Preclinical Research Gabapentin is an anticonvulsant used to treat neuropathic pain. Mangiferin is an antioxidant that has antinociceptive and antiallodynic effects in inflammatory and neuropathic pain models. The purpose of this study was to determine the interaction between mangiferin and gabapentin in the development and maintenance of formalin-induced secondary allodynia and hyperalgesia in rats. Gabapentin, mangiferin, or their fixed-dose ratio combination were administrated peripherally. Isobolographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The above results reveal persistent hyperactivity of sensory ganglion neurons over months after formalin injection, which may contribute to the development of chronic pain. Previous studies have shown that formalin-induced pain may persist for days after the initial injection 42,43 . Because formalin-induced spontaneous licking or flinching behavior was no longer present after the day of injection, we employed a two-compartment conditional place preference (CPP) test 44 to assess the presence or absence of ongoing pain 45 .…”
Section: Resultsmentioning
confidence: 99%
“…The above results reveal persistent hyperactivity of sensory ganglion neurons over months after formalin injection, which may contribute to the development of chronic pain. Previous studies have shown that formalin-induced pain may persist for days after the initial injection 42,43 . Because formalin-induced spontaneous licking or flinching behavior was no longer present after the day of injection, we employed a two-compartment conditional place preference (CPP) test 44 to assess the presence or absence of ongoing pain 45 .…”
Section: Resultsmentioning
confidence: 99%